The Effect of Estradiol on Production of Type II Collagen and Aggrecan in Chondrogenic Proccess - Batool Hashemibeni; Farzaneh Sadeghi; Azadeh Kabiri; Malekmasud Ansar (مجله دانشکده پزشکی اصفهان, 2014)
Background: Sex hormones play important role in proliferation, differentiation, maturation and the scheduled death of chondrocytes. Although, some studies report the regulatory role of estrogen in the development and progression of cartilage, some of the mechanisms still remain unclear, including the role of estrogen in the expression of cartilage-specific genes in chondrogenesis process. We studied this role in the present study.